Nature of hematopoietic system alteration and organ damage induced by fungal filtrate of Pestalotiopsis microspora in vivo - Taofeeq Garuba, Adebola Azeez Lateef, Soliu Abiola Atunwa, Abibat Yetunde Lateef, Olajumoke Oluwabunmi Kolawole, Saheed Sabiu (Journal of Applied Pharmaceutical Science, 2021)
Pestalotiopsis microspora is an endophytic producer of bioactive compounds of therapeutic importance. Despite its therapeutic and industrial applications, its safety profile in animals including humans remains elusive. This study investigated the nature of acute and repeated dosing toxicity of P. microspora filtrate (PMF) on the hematological parameters and vital metabolic organs in vivo. For the acute testing, the animals were administered a single oral dose (2 ml/kg b.w.) of PMF and observed for 14 days for probable signs of toxicity. Repeated dosing was carried out by once daily oral gavaging with graded doses (0.25, 0.5, and 0.75 ml/kg b.w.) of PMF for 28 days. Throughout the two experimental periods, no deleterious behavioral changes and clinical signs of toxicity were observed. However, except for the significant differences (p < 0.05) in the body weight, platelet, and white blood cell counts of the PMF-treated animals relative to the control, data obtained on the hematological parameters of the PMF-administered rats compared favorably with those of the control group in the 28-day toxicity assay. This observation suggests parameters-specific toxicity and was supported by the PMF-induced necrosis and cytoarchitectural distortions in the organs of the animals. Study to confirm the presence of toxins/antinutritional factors in PMF to better understand its toxicological dynamics is imperative.
Keywords: Ascomycetes, endophytes, organ damage, Pestalotiopsis microspora, selective toxicity.